DEVELOPMENT OF ALLOTHERMAL GASIFICATION BY A DUAL FLUIDIZED BED TECHNOLOGY - Dahlia Diniyati; Nurhadi Nurhadi (Puslitbang tekMIRA, 2014)
Allothermal gasification is a gasification process which separates oxidation process and other processes. So that, synthesis gas (syngas) could be produced from gasification with air as gasification agent. The main feature of allothermal gasification is how to transfer the heat of oxidation reaction to supply heat required for drying, pyrolysis and reduction processes. One of the techniques is to circulate bed material using a dual fluidized bed. Pressure loop and syngas composition resulted from gasification test is discussed. Pressure loop data of the Process Development Unit (PDU) facility showed a stable condition and resulted a continous circulation of the bed material. Therefore, heat transfer of oxidation reaction into a gasifier proceeded in a continous and stable way. A good heat transfer of the heat of oxidation reaction resulted a good quality of syngas where the composi- tion of H2 was close to 50% and the ratio of H2/CO was >2% which is suitable for chemical feedstock